Metal tolerance of Río Tinto fungi - Oggerin, Monike; del Moral, Catalina; Rodriguez, Nuria; Fernandez-Gonzalez, Nuria; Martínez, José Manuel; Lorca, Iván; Amils, Ricardo (Frontiers in Fungal Biology, 2024)
South-West Spain’s Río Tinto is a stressful acidic microbial habitat with a noticeably high concentration of toxic heavy metals. Nevertheless has an unexpected degree of eukaryotic diversity in its basin, with a high diversity of fungal saprotrophs. Although some studies on the eukaryotic diversity in Rio Tinto have been published, none of them has used molecular methodologies to describe the fungal diversity and taxonomic affiliations that emerge along the river at different seasons. The aim of the present study was to isolate and describe the seasonal diversity of the fungal community in the Río Tinto basin and its correlation with the physico-chemical parameters existing along the river’s course. The taxonomic affiliation of 359 fungal isolates, based on the complete internal transcribed spacer DNA sequences, revealed a high degree of diversity, identifying species belonging primarily to the phylum Ascomycota, but representatives of the Basidiomycota and Mucoromycota were also present. Forty representative isolates along the river were evaluated for their tolerance to toxic heavy metals. Some of the isolates were able to grow in the presence of 1000 mM of Cu2+, 750 mM of As5+and Cd2+, and 100 mM of Co2+, Ni2+ and Pb2+.